2021
DOI: 10.3389/fgene.2021.683959
|View full text |Cite
|
Sign up to set email alerts
|

Camk2a-Cre and Tshz3 Expression in Mouse Striatal Cholinergic Interneurons: Implications for Autism Spectrum Disorder

Abstract: Camk2a-Cre mice have been widely used to study the postnatal function of several genes in forebrain projection neurons, including cortical projection neurons (CPNs) and striatal medium-sized spiny neurons (MSNs). We linked heterozygous deletion of TSHZ3/Tshz3 gene to autism spectrum disorder (ASD) and used Camk2a-Cre mice to investigate the postnatal function of Tshz3, which is expressed by CPNs but not MSNs. Recently, single-cell transcriptomics of the adult mouse striatum revealed the expression of Camk2a in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…This was preferred to dual immunodetection of CHAT and TSHZ3 since the tissue fixation conditions for obtaining optimal detection of each protein are different, and also because TSHZ3 immunodetection provides weaker labeling and higher background than ß-Gal immunodetection. As reported previously [ 13 ], virtually all SCINs, both in the dorsal striatum and the nucleus accumbens, express Tshz3 (Fig. S6a, h ).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…This was preferred to dual immunodetection of CHAT and TSHZ3 since the tissue fixation conditions for obtaining optimal detection of each protein are different, and also because TSHZ3 immunodetection provides weaker labeling and higher background than ß-Gal immunodetection. As reported previously [ 13 ], virtually all SCINs, both in the dorsal striatum and the nucleus accumbens, express Tshz3 (Fig. S6a, h ).…”
Section: Resultssupporting
confidence: 86%
“…We previously reported that around 90% of the Tshz3 -expressing cells in the striatum are SCINs [ 13 ]. Using Tshz3 +/lacZ ;GAD67-GFP mice, we found here that GABAergic neurons constitute 9.7 ± 1.3% ( n = 21 sections from 3 mice) of the striatal Tshz3 population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations